Partially coherent radar unties range resolution from bandwidth limitations - Rony Komissarov (Nature Portfolio, 2019)
Distinguishing between closely situated targets depends inversely on the bandwidth of the transmitted radar signal. Here, the authors demonstrate a type of ranging system which is not limited by bandwidth. They show an improvement of two orders of magnitude, compared to standard coherent radars with the same bandwidth.